A Systematic Review of Hypnosis for Clinical Pain Relief - Titus H. Yim; Stuart W. G. Derbyshire (European Journal of Pain, 2026)
ABSTRACT Background Previous reviews report moderate reductions in clinical pain with hypnotic suggestion but provide only partial views by comparing hypnosis with inactive controls alone or including few studies or mixed control groups. This review comprehensively evaluated the efficacy of hypnosis in reducing clinical pain intensity compared with non‐active and active controls. Methods Systematic review following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) review guidelines with comprehensive literature search and meta‐analysis. A total of 106 studies met inclusion criteria; 104 effect sizes from 84 studies were pooled using random‐effects models, and 22 studies were narratively synthesised. Five databases were searched from inception to October 2025 for randomised controlled trials evaluating hypnosis versus non‐active or active non‐pharmacological controls for clinical pain intensity. Two independent reviewers screened articles and extracted data using standardised tools. Results Meta‐analysis of 57 studies (4572 participants) showed reduced post‐intervention pain following hypnosis versus non‐active controls (SMD −0.33). Pre–post change scores yielded a comparable but non‐significant effect (SMD −0.31). Subgroup analyses showed no differences by pain type, control type or delivery mode. Hypnosis did not outperform active controls, including relaxation (14 studies, SMD −0.13), pain education (7 studies, SMD −0.17 to −0.19) or cognitive‐behavioural therapy (5 studies, SMD −0.32). Conclusions Hypnosis yields modest reductions in clinical pain comparable to other psychological interventions. Significance Statement This review provides a comprehensive synthesis of randomised trials evaluating hypnosis for clinical pain intensity, distinguishing non‐active from active comparators and examining delivery mode, pain type and risk of bias. Hypnosis produced only small reductions in pain and did not clearly outperform relaxation, pain education or cognitive‐behavioural therapy. These findings refine expectations for hypnoanalgesia, suggesting it may provide low‐risk supportive care for selected patients, but should not be presented as a reliably superior pain‐reduction treatment option. Trial Registration Prospero (CRD42024608722)